USMONIYLAR IMPERIYASINING TANZIMOT DAVRI ISLOHOTLARI - Xurramova Komila Baxrom qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article discusses the specifics of the reforms of the Tanzimat period of the Ottoman Empire, the gradual foundations of the renewal of the socio-economic, political, and cultural spheres of the Ottoman Empire. It also provides important and interesting information about the regulation of reforms in state administration and the military sphere.